ANALYZING SERVICE QUALITY AND PRICE TOWARDS CUSTOMERS SATISFACTION AT ASTON MANADO HOTEL - Riefad, Muh. Riefky; Pangemanan, Sifrid S.; Tumbuan, Willem J. F. Alfa (Universitas Sam Ratulangi, 2020)
The development of the hotel and tourism business in Indonesia has increased in recent years. The hospitality industry is one of the facilities which support the success of tourism. The hospitality industry is developing very fast, not only in Indonesian but also entire world and they does not only using hotel as a place to stay while on vacation, but also for business purposes, seminar, and exhibitions. North Sulawesi as one of the region in Indonesia that has a lot of tourism potential. Aston Manado Hotel is one of the hospitality service provider companies that prioritizes service to their customers. This research aimed to analyze the service quality and price towards customer satisfaction. The population of this research is the Aston Manado Hotel customers with sample size as many as 50 respondents. The finding resulted shows that service quality has a positive and significant effect towards customer satisfaction. In a sense, it is proven that customer satisfaction influence and correlate with service quality. The price is also one of the main considerations of customers to get satisfaction, with consideration of affordable price yet synergize with an adequate services and facilities in order to maintain customer satisfaction.Â Keyword: Customers Satisfaction, Service Quality, Price, Ordinary Least SquareANALISIS KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN DI ASTON MANADO HOTEL